2010
DOI: 10.1093/mutage/geq024
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of baseline and induced DNA damage in human sperm exposed to benzo[a]pyrene or its metabolite benzo[a]pyrene-7,8-diol-9,10-epoxide, using the comet assay

Abstract: Exposure to genotoxins may compromise DNA integrity in male reproductive cells, putting future progeny at risk for developmental defects and diseases. To study the usefulness of sperm DNA damage as a biomarker for genotoxic exposure, we have investigated cellular and molecular changes induced by benzo[a]pyrene (B[a]P) in human sperm in vitro, and results have been compared for smokers and non-smokers. Sperm DNA obtained from five smokers was indeed more fragmented than sperm of six non-smokers (mean % Tail DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 53 publications
(50 reference statements)
6
37
1
Order By: Relevance
“…The protocol was based on Sipinen et al [19]. Slides were precoated with agarose by dipping into a vertical staining jar of melted 1% standard agarose in water.…”
Section: Single Cell Gel Electrophoresis Assay (Comet Assay)mentioning
confidence: 99%
“…The protocol was based on Sipinen et al [19]. Slides were precoated with agarose by dipping into a vertical staining jar of melted 1% standard agarose in water.…”
Section: Single Cell Gel Electrophoresis Assay (Comet Assay)mentioning
confidence: 99%
“…Benzo(a)pyrene (Bap), a prototype of polycyclic aromatic hydrocarbon (PAH) that is released into the environment by industrial emission, has attracted worldwide attention as its toxic effect on male reproduction. It has been demonstrated that Bap can cause seminiferous tubules malformation, change the epididymis function and enzyme activity in testicular cells, induce DNA damage and synthesis inhibition in spermatogenic cells, and decrease serum testosterone level and the amount of spermatogenic cells and sperms (Zhu et al, 2010;Sipinen et al, 2010;Inyang et al, 2003;Mohammad Shah Alam et al, 2010;Ramesh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In studies that quantify BPDE-DNA adducts, sperm are selected from either untreated semen samples (12) or semen treated by a swim-up (3,5) or DGC (13) procedure. To our knowledge, no study has been conducted to compare BPDE-DNA adduct levels in selected and nonselected sperm.…”
mentioning
confidence: 99%